2020
DOI: 10.24815/siele.v7i1.15170
|View full text |Cite
|
Sign up to set email alerts
|

Social practice on Facebook: Critical discourse analysis in the process of text production

Abstract: The study aims to identify the ways to produce text production process by Universitas Islam Negeri (UIN, or State Islamic University) students in Padang on Facebook. Documentations, observations, and in depth-interviews were used to collect data. There were 1,214 discourses found on group and personal accounts of 27 informants, and 400 discourses were taken as data of the research. The analysis was conducted by following Fairclough’s Critical Discourse Analysis, (CDA), with the Critical Linguistics approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Some other specific studies have addressed various integration of technology in EFL instruction (Chen et al, 2019;Hsieh et al, 2017;Triana et al, 2020). Triana et al (2020) informed the use of social media among students in higher education on Facebook conducted in three ways: creating their own text, informing other people's texts shared from the site, and producing text adapted from other texts.…”
Section: Technology Integration and Eflmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other specific studies have addressed various integration of technology in EFL instruction (Chen et al, 2019;Hsieh et al, 2017;Triana et al, 2020). Triana et al (2020) informed the use of social media among students in higher education on Facebook conducted in three ways: creating their own text, informing other people's texts shared from the site, and producing text adapted from other texts.…”
Section: Technology Integration and Eflmentioning
confidence: 99%
“…Some other specific studies have addressed various integration of technology in EFL instruction (Chen et al, 2019;Hsieh et al, 2017;Triana et al, 2020). Triana et al (2020) informed the use of social media among students in higher education on Facebook conducted in three ways: creating their own text, informing other people's texts shared from the site, and producing text adapted from other texts. Meanwhile, Hsieh et al (2017) reported the positive effects of the mobile-based flipped approach over the conventional lecture-based and the role of attitude on the LINE use in learners' subsequent behavioral intention regarding technology integration in language learning.…”
Section: Technology Integration and Eflmentioning
confidence: 99%
“…More importantly, Facebook functions as a melting-pot for its users to spread their ideas, share news, and meet people with diverse sociocultural backgrounds and geographical locations. In short, Facebook has developed as an innovative means of communication through which individuals can actualize their desires to connect and share information using the different tools and features offered by Facebook (Triana, et al, 2020).…”
Section: Facebook Language: a New Netspeakmentioning
confidence: 99%
“…(2016) stated that language is the main aspect of culture on one side, and on the other side, the norms and values cannot be separated from language. In this context, the language used in birthday wishes by generation Z is the manifestation of socio-cultural practices (Triana, et. al., 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%